2020
DOI: 10.21776/ub.jitek.2020.015.01.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotic in Milk Fermentation Towards Decreasing Cholesterol Levels: in Vivo Studies

Abstract: Hypercholesterolemia is a disease that is indicated by the increasing level of cholesterol in the body and also as one of the factors causing cardiovascular disease. An alternative that can be done to prevent hypercholesterolemia is by consuming fermented milk. Skim milk is fermented using probiotic of Lactobacillus acidophillus, Lactobacillus plantarum and Streptococcus thermophilus. The skimmed milk that has been fermented is then tested for total lactic acid bacteria, total acid, pH, and in vivo analysis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…The acidity of fermented milk is caused by the breakdown of lactose by lactic acid bacteria. The total titrated acid was determined by acid-base titration to measure the total acid concentration (Andriani et al, 2020). The titratable acidity of fermented milk results from this study is almost the same as research conducted by (Susmiati et al, 2022), and Melia et al (2021).…”
Section: Titratable Aciditysupporting
confidence: 57%
“…The acidity of fermented milk is caused by the breakdown of lactose by lactic acid bacteria. The total titrated acid was determined by acid-base titration to measure the total acid concentration (Andriani et al, 2020). The titratable acidity of fermented milk results from this study is almost the same as research conducted by (Susmiati et al, 2022), and Melia et al (2021).…”
Section: Titratable Aciditysupporting
confidence: 57%
“…A previous study showed that the fermentation process, which results from the accumulation of acids from LAB, lowers the pH level. Protein is used to promote the growth of LAB, which use lactose as a carbon source and produce lactic acid as a metabolite, which lowers the pH level [30].…”
Section: Physicochemical and Proximate Composition Of Fermented Skimm...mentioning
confidence: 99%
“…Probiotics from the lactic acid bacteria (LAB) have been incorporated into a wide variety of functional foods; this is to increase the nutritional value and health benefits of these foods. Results from in vitro and in vivo assays suggest that probiotics can be used to help lower cholesterol levels and prevent metabolic syndrome (Li et al 2019;Andriani et al 2020). To fully examine their health effects in the human body, LAB should be viable, present in high numbers, and be able to colonize the gastrointestinal (GI) tract (Nuraida et al 2011;Maryati et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Pediococcus and Lactobacillus have been identified as among the LAB genera with probiotic characteristics. Lactobacillus species, such as L. casei strain Shirota, L. casei strain Zhang (Wang et al 2013), L. rhamnosus (Koskenniemi et al 2011), L. paracasei, L. plantarum (Buntin et al 2017, and L. casei strain AP (Afidah et al 2019), have been shown to function as probiotics. Meanwhile, P. pentosaceous K23-3 is an example of a Pediococcus strain shown to have probiotic properties (Shin et al 2008).…”
Section: Introductionmentioning
confidence: 99%